2022
DOI: 10.1002/da.23291
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making biases in suicide attempters with major depressive disorder: A computational modeling study using the balloon analog risk task (BART)

Abstract: Background In the last decade, suicidality has been increasingly theorized as a distinct phenomenon from major depressive disorder (MDD), with unique psychological and neural mechanisms, rather than being mostly a severe symptom of MDD. Although decision‐making biases have been widely reported in suicide attempters with MDD, little is known regarding what components of these biases can be distinguished from depressiveness itself. Methods Ninety‐three patients with current MDD (40 with suicide attempts [SA grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…Our study also shows a significant inter-correlation between psychological pain avoidance and loss aversion ( r = 0.31, p = 0.004), and initial belief of burst ( r = −0.30, p = 0.005), reproducing a prior finding [44]. Daniel and colleagues reported that individuals who are ready to commit suicide have a tendency to exaggerate their perceived losses and minor losses are perceived as being so overwhelming that they reinforce their suicide behavior [52].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study also shows a significant inter-correlation between psychological pain avoidance and loss aversion ( r = 0.31, p = 0.004), and initial belief of burst ( r = −0.30, p = 0.005), reproducing a prior finding [44]. Daniel and colleagues reported that individuals who are ready to commit suicide have a tendency to exaggerate their perceived losses and minor losses are perceived as being so overwhelming that they reinforce their suicide behavior [52].…”
Section: Discussionsupporting
confidence: 88%
“…Our study's finding that the SA group had higher psychological pain avoidance than the HSI group is consistent with those reported by Li and colleagues [25,49]. In terms of risk decision-making, our finding that the SA group had greater loss aversion than the HSI group is similar to those from Liu and colleagues using similar methodology [44], and others employing different decision tasks or models [26,50]. Furthermore, the SA group showed a lower estimation of the probability of balloon explosion than the HSI group, which is consistent with the results of Liu et.…”
Section: Pain Avoidance and Risk Decision-makingsupporting
confidence: 92%
See 1 more Smart Citation
“…However, each pump increases the chance of the balloon bursting. Other studies, however, showed higher levels of risk-taking on the BART in depressed individuals compared to healthy controls 10 .…”
Section: Depression and Risk-taking In Adulthoodmentioning
confidence: 85%
“…concept of negativity bias refers to the assumption that adverse circumstances are generally more substantial, potent, capturing in combinations, and resourceful than their positive counterparts (Abdou et al, 2022). The principle of loss aversion in prospect theory is relevant to this negativity bias, which holds that people are more motivated by the threat of loss than by the promise of gain (Liu et al, 2022). People in high-income countries have more to lose due to economic uncertainty than those in the middle-and low-income countries; thus, it stands to reason that this is where we see the strongest association between economic uncertainty and suicide.…”
Section: Tablementioning
confidence: 99%